Students’ Independent Work in Studying Foreign Language based on LMS MOODLE - Hontarenko, Iryna (Educational Challenges, 2022)
This article provides an overview of the Moodle learning environment – what it includes and how it can benefit your teaching. The purpose of the article is to substantiate the significance and expediency of using electronic educational courses on the LMS MOODLE platform in the context of improving the quality of independent work of students while learning a foreign language. The following methods were used: theoretical (analysis, synthesis, generalisation and systematisation of scientific theoretical and methodological literature) – in order to define the concepts of research; empirical-diagnostic (discussions, questioning, testing, pedagogical observation, expert questionnaire) to study the results of educational activities and determine the level of formation of students’ independent work; pedagogical experiment (stages of launching, formation, controlling) to check the performance of the system of the corresponding didactic tools based on the LMS MOODLE platform. The results are the following. Nowadays, universities widely use the e-learning system based on the virtual learning environment Moodle (full name – Modular object-oriented dynamic learning environment). It is focused on learning technologies in cooperation and allows you to organise training in the process of solving educational tasks together, exchange knowledge. A brief analysis of the main directions of distance learning is given; experience in the development and application of electronic educational courses in English. It is concluded that the use of e-learning in the educational process increases the effectiveness of various types of independent activity of students, self-development and formation of their professional competence. The author has developed an electronic course on the discipline “Foreign language of academic and professional communication” using LMS Moodle. Thus, it is concluded that LMS Moodle has increased the effectiveness of learning a foreign language by non-linguistic students. Learning becomes oriented due to the variability and flexibility of learning the learning material at an individual pace. In addition, LMS Moodle allows solving a variety of priority tasks that modern society puts before learning and meets the requirements and capabilities of recent students. However, like any method, distance learning has its strengths and weaknesses.